Angiotensin II Type 1 Receptor Gene A1166C Polymorphism In Hypertension : A Study On Its Influence On Aortic Stiffness And Response To Antihypertensive Therapy Among Malays - Rehman, Asia (2005)
Hypertension is a major contributor to cardiovascular disease (CVD) which is the leading cause of death in Malaysia.Hipertensi merupakan penyumbang utama kepada penyakit kardiovaskular yang merupakan penyebab utama kematian di Malaysia.